(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed to evaluate the effect of Teucrium stocksianum on angiogenesis by using chorioallantoic membrane (CAM) assay. Fertilized eggs were incubated on the 5th day and dose of different dilutions 0.03%, 0.05%, 0.1%, and 0.5% of the plant extract was applied on 6th day. Evaluation of primary, secondary and tertiary blood vessels diameter and CAM area on 7th day by SPIP software. T. stocksianum showed antiangiogenic effect by reducing the diameter of CAM of blood vessels by applying the dilutions while significant results were obtained at dilution of 0.5%.